Pistoleros and popular movements : the politics of state formation in postrevolutionary Oaxaca - Smith, Benjamin T. (Mexican experience., 2009)
The postrevolutionary reconstruction of the Mexican government did not easily or immediately reach all corners of the country. At every level, political intermediaries negotiated, resisted, appropriated, or ignored the dictates of the central government. National policy reverberated through Mexico?s local and political networks in countless different ways and resulted in a myriad of regional arrangements. It is this process of diffusion, politicking, and conflict that Benjamin T. Smith examines in Pistoleros and Popular Movements.